Physiology of High-Altitude Acclimatization: Review Article - Elawad, Bahaeldean E. (British Journal of Healthcare and Medical Research, 2024)
As the barometric pressure decreases exponentially within the troposphere, the partial pressure of oxygen decreases proportionally in ambient air, inspired air, alveolar air, and arterial blood. The primary physiologic challenge with altitude is reduced partial pressure of oxygen (hypobaric hypoxia). Physiologic adaptation to decreasing partial pressure of oxygen in the high altitude environment is known as acclimatization. It is a complex, not yet fully understood, mechanism to preserve cell function despite reduced oxygen supply to the tissues. Chronic adaptation includes improving oxygen transport capacity and restoring oxygen delivery to the tissues. Of the three successful patterns of adaptation to chronic high altitude hypoxia; the Amharas have the legend one. Normal partial pressure of oxygen in arterial blood despite inevitable hypobaric reduction of partial pressure of oxygen in inspired air is a puzzler and big challenge to respiratory physiology. Amharas have elevated nitric oxide which suggests the possibility of adaptation via vasodilatation, which would increase oxygen supply tometabolic tissues. Left shift of ODC under influence of nitric oxide seems to be an integral component of Amharic pattern of adaptation. The mechanism of which is not known. It could be hypothesized that native Amhara highlanders have increased, pulmonary capillary transit times; finite reaction of hemoglobin with oxygen; and oxygen-carrying capacity of hemoglobin than other high altitude populations. Further research is warranted to explore the physiologic mechanism by which Amhara highlanders maintain normal PaO2 despite hypobaric hypoxia. This is a potential breakthrough in management of critically ill hypoxic patients at intensive care settings.